Lifespan brain age prediction based on multiple EEG oscillatory features and sparse group lasso - Shiang Hu; Xue Xiang; Xiaolong Huang; Yan Lu; Xulai Zhang; Dezhong Yao; Pedro A. Valdes-Sosa (Frontiers in Aging Neuroscience)
IntroductionThe neural dynamics underlying cognition and behavior change greatly during the lifespan of brain development and aging. EEG is a promising modality due to its high temporal resolution in capturing neural oscillations. Precise prediction of brain age (BA) based on EEG is crucial to screening high-risk individuals from large cohorts. However, the lifespan representation of the EEG oscillatory features (OSFs) is largely unclear, limiting practical BA applications in clinical scenarios. This study aims to build an interpretable BA prediction model through prior knowledge and sparse group lasso.MethodsBased on the multinational cross-spectral (MNCS) dataset that covers 5–97 years, (1) we extracted four groups of OSFs, such as aperiodic parameters, periodic parameters, power-ratio, and relative power; (2) the OSFs trajectories evolving with age and the OSF importance topographies were mapped using the generalized additive model for location, scale and shape (GAMLSS) and Pearson's correlation coefficient (PCC); (3) the inter-oscillatory dependency coefficients (ODCs) were extracted by the sparse group lasso; (4) the fusion of OSFs and ODCs was flattened and fed into a three-layer fully connected neural network (FCNN); the FCNN interpretability was analyzed by Layerwise Relevance Propagation and 10-fold cross-validation.ResultsThe results showed that the FCNN model that incorporated ODC significantly improved the prediction of BA (MAE = 2.95 years, R2 = 0.86) compared to the use of only OSF (MAE = 3.44 years, R2 = 0.84).DiscussionIn general, this study proposed a BA prediction model named NEOBA by systematically employing OSFs and highlighting the interpretability of the model, which holds broad promise by integrating normative modeling for precise individual stratification.